The fate of side branches covered by flow diverters: results from 140 patients - Bhogal, Pervinder; Bäzner, Hansjörg (World neurosurgery, 2017)
Background: Flow diverter stents (FDS) are a recognized treatment option for intracranial aneurysms. There remain ongoing concerns regarding the safety of FDS, especially regarding the fate of covered side branches. We report the patency of side branches covered by FDS. Methods: We retrospectively reviewed our database of prospectively collected information for all patients treated with FDS for an unruptured saccular aneurysm of the clinoid, ophthalmic, and terminating segments of the internal carotid artery between September 2009 and July 2016. The aneurysm location, fundus size, and the state of covered branches at last angiography were recorded compared with preoperative angiography. Results: We identified 140 patients, with 147 aneurysms, who met our inclusion criteria. Five patients had bilateral aneurysms. There were 31 male patients in our cohort (21.9%) and the mean average age was 56.2 ± 13.7 years. Sixty-seven aneurysms arose from the communicating, 58 from the ophthalmic, and 22 from the clinoidal segments. At last follow-up (mean, 22.3 months) 116 aneurysms were completely occluded (78.3%). On the most recent angiogram, 7 ophthalmic (5.3%), 20 posterior communicating (42.6%), 0 anterior choroidal (0%), and 2 anterior cerebral arteries (14.3%) were completely occluded. Reduced vessel caliber was seen in 11 ophthalmic (8.3%), 3 posterior communicating (6.4%), 0 anterior choroidal, and 6 anterior cerebral arteries (42.9%). One patient died during follow-up. Conclusions: The side branch occlusion rate was 20% and included ophthalmic, posterior communicating, and anterior cerebral arteries. Consistent with other studies, we did not see occlusion of the anterior choroidal artery.